2019
DOI: 10.1159/000499858
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Staphylococcus epidermidis</i></b>: A Potential New Player in the Physiopathology of Acne?

Abstract: Background: Cutibacterium acnes has been identified as one of the main triggers of acne. However, increasing knowledge of the human skin microbiome raises questions about the role of other skin commensals, such as Staphylococcus epidermidis, in the physiopathology of this skin disease. Summary: This review provides an overview of current knowledge of the potential role of S. epidermidis in the physiopathology of acne. Recent research indicates that acne might be the result of an unbalanced equilibrium between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 77 publications
0
78
0
4
Order By: Relevance
“…epidermidis was the second most prevalent microbiota (19%) before treatment and became the most prevalent bacteria (28%) after treatment. S. epidermidis and C. acnes use glycerol as a shared carbon source to generate different short-chain fatty acids used as antimicrobial agents to compete against each other [26]. Different in vivo antagonism investigations demonstrated that S. epidermidis controls the proliferation of C. acnes via the release of succinic acid, a fatty acid fermentation product, which blocks surface toll-like receptors (TLRs) of keratinocytes and tumor necrosis factor and suppresses C. acnes-induced IL-6 [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…epidermidis was the second most prevalent microbiota (19%) before treatment and became the most prevalent bacteria (28%) after treatment. S. epidermidis and C. acnes use glycerol as a shared carbon source to generate different short-chain fatty acids used as antimicrobial agents to compete against each other [26]. Different in vivo antagonism investigations demonstrated that S. epidermidis controls the proliferation of C. acnes via the release of succinic acid, a fatty acid fermentation product, which blocks surface toll-like receptors (TLRs) of keratinocytes and tumor necrosis factor and suppresses C. acnes-induced IL-6 [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, some C. acnes phylogroups encode biosynthesis genes for a thiopeptide with possible antimicrobial activity against S. epidermidis, which conversely secretes bacteriocins such as epidermin that kills C. acnes 32 . The antagonism between S. epidermidis and C. acnes is also noted in acne vulgaris, in which not only SCFAs but many factors like antimicrobial peptides secreted from keratinocytes have an impact 33 . Considering that S. epidermidis also produces SCFAs, further study of additional, unidentified factors other than SCFAs should be addressed in the future.…”
Section: Control Scfasmentioning
confidence: 99%
“…n -Butyric acid ( 47 ) is a short-chain fatty acid reported as metabolite of Staphylococcus epidermidis , a skin probiotic bacterium ( Claudel et al, 2019 ; Traisaeng et al, 2019 ). n -butyric acid has been reported to inhibit HDAC, DNA synthesis, and cell growth in colon tumor cell lines ( Andriamihaja et al, 2009 ; Zhang et al, 2010 ; Traisaeng et al, 2019 ).…”
Section: Hdac Inhibitorsmentioning
confidence: 99%